Design of gas concentration measurement and monitoring system for biogas power plant - Iswanto Iswanto; Alfian Ma’arif; Bilah Kebenaran; Prisma Megantoro (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Biogas is a gas obtained from the breakdown of organic matter (such as animal waste, human waste, and plants) by methanogenic bacteria in an oxygen-free (anaerobic) state. The biogas produced mainly consists of 50-70% methane, 30-40% carbon dioxide, and other gases in small amounts. The gas produced has a different composition depending on the type of animal that produces it. It is challenging to obtain biogas concentration data because the monitoring equipment is currently minimal. Therefore, this research discusses how to make a monitoring system for biogas reactors. Sensors are installed in the digester tank and storage tank. The installed sensors are the MQ-4 sensor to detect methane gas (CH4), MG-811 sensor to detect carbon dioxide (CO2) gas, MQ-136 sensor to detect sulfide acid gas (H2S), and Thermocouple Type-K to detect temperature. The sensor will send a signal to the control unit in Arduino Mega 2560, then processed and displayed on the liquid crystal display (LCD). The sensor calculation results' accuracy is not much different from the reference based on the sensor readings. The sensor deviation standard is below 5.0, indicating that the sensor is in precision. The sensor's linearity of MQ-4 is 0.7%, the MG-811 is 0.17%, the MQ-136 is 0.29%, and the Type-K Thermocouple is 1.19%. The installed sensor can be used to monitor gas concentration and temperature in a biogas reactor.